On the rule of mixtures for bimetal composites without bonding - Bo Feng; Xiaowei Feng; Changjian Yan; Yunchang Xin; Haiyan Wang; Juan Wang; Kaihong Zheng (Journal of Magnesium and Alloys, 2020)
In the present study, three types of bimetal composites, Al 6082 sleeve/Al 6082 core, Mg AZ31 sleeve/Mg AZ31 core and Al 6082 sleeve/Mg AZ31 core, were fabricated by drilling and assembling. The rule of mixtures (ROM) for the flow curves and yield strengths during compressive test were addressed. Our results show that the ROM can predict well the experimental flow curves and yield strengths of bimetal composites without bonding, irrespectively of the different strain hardening behavior between the two components.